Antibiotic prophylaxis of infective endocarditis in patients with predisposing cardiac conditions: French cardiologists' implementation of current guidelines. (15th January 2020) - Cloitre, A.; Lesclous, P.; Trochu, Q.; Selton-Suty, C.; Boutoille, D.; Le Tourneau, T.; Delahaye, F.; Thomas, D.; Iung, B.; Gaudin, A.; Duval, X.; Trochu, J.N.
Abstract: Background: To prevent infective endocarditis (IE), with the exception of the United Kingdom, antibiotic prophylaxis (AP) is recommended in patients with predisposing cardiac conditions (PCCs) worldwide. To conclude on the relevance of this strategy, how the current guidelines are applied is a crucial point to investigate. The first aim of this study was to assess cardiologists' implementation of the current guidelines. The secondary objective was to identify specific areas where the training and knowledge of French cardiologists could be improved. Methods: A national online survey was carried out among the 2228 cardiologist members of the French Society of Cardiology. Results: The high risk PCCs for which IE AP is recommended were correctly identified by the vast majority of the respondents so that IE AP is mostly prescribed correctly in such patients. But only 12% identified all the right indications for IE AP according to 13 predefined PCCs (3 at high-risk, 6 at moderate-risk and 4 at low-risk of IE) so that some IE AP misuses are recorded, overprescription in particular. Only 47% prescribed the proper amoxicillin schedule and only 15% prescribed the appropriate clindamycin schedule in cases with penicillin allergy. Conclusion: This study evidenced relevant areas where the training of cardiologists could be improved such as knowledge of the risk of IE for certain PCCs and some common invasive dental procedures. Cardiologists' knowledge should be improved before any conclusion can be drawn on the relevance of this AP strategy and its influence on IE incidence. Highlights: There is a low level of implementation of ESC guidelines regarding AP for IE Need to improve compliance with guidelines by sustaining continuous medical education. Need to strengthen the dialogue between cardiologists and dentists